Identification of Glutathione S-Transferase Genes in Hami Melon (Cucumis melo var. saccharinus) and Their Expression Analysis Under Cold Stress - Song, Wen; Zhou, Fake; Shan, Chunhui; Zhang, Qin; Ning, Ming; Liu, Xiumin; Zhao, Xinxin; Cai, Wenchao; Yang, Xinquan; Hao, Guangfei; Tang, Fengxian (Frontiers in Plant Science, 2021)
As a group of multifunctional enzymes, glutathione S-transferases (GSTs) participate in oxidative stress resistance and cellular detoxification. Here, we identified 39 CmGST genes with typical binding sites from the Hami melon genome and they can be classified into seven subfamilies. Their molecular information, chromosomal locations, phylogenetic relationships, synteny relationships, gene structures, protein-protein interactions (PPI), structure of 3D models and expression levels under cold stress were analyzed. Expression analysis indicated that cold-tolerant Jia Shi-310 (JS) had higher GST enzyme activities and expression levels of 28 stress-related genes under cold stress. Some CmGSTs belonging to Tau, Phi and DHAR classes played significant roles under cold stress and they could be regarded as candidate genes for further studies. The present study systematically investigated the characterization of Hami melon GST gene family, extending our understanding of Hami melon GST mediated stress-response mechanisms in this worldwide fruit.